Immunohistochemical localization of the NH(2)-terminal and COOH-terminal fragments of dentin sialoprotein in mouse teeth - Yuan, Guohua (2012)
Dentin sialoprotein (DSP) is a major non-collagenous protein in dentin. Mutation studies in human, along with gene knockout and transgenic experiments in mice, have confirmed the critical role of DSP for dentin formation. Our previous study reported that DSP is processed into fragments in mouse odontoblast-like cells. In order to gain insights into the function of DSP fragments, we further evaluated the expression pattern of DSP in the mouse odontoblast-like cells using immunohistochemistry and western blot assay with antibodies against the NH(2)-terminal and COOH-terminal regions of DSP. Then, the distribution profiles of the DSP NH(2)-terminal and COOH-terminal fragments and osteopontin (OPN) were investigated in mouse teeth at different ages by immunohistochemistry. In the odontoblast-like cells, multiple low molecular weight DSP fragments were detected, suggesting that part of the DSP protein was processed in the odontoblast-like cells. In mouse first lower molars, immunoreactions for anti-DSP-NH(2) antibody were intense in the predentin matrix but weak in mineralized dentin; in contrast, for anti-DSP-COOH antibody, strong immunoreactions were found in mineralized dentin, in particular dentinal tubules but weak in predentin. Therefore, DSP NH(2)-terminal and COOH-terminal fragments from odontoblasts were secreted to different parts of teeth, suggesting that they may play distinct roles in dentinogenesis. Meanwhile, both DSP antibodies showed weak staining in reactionary dentin (RD), whereas osteopontin (OPN) was clearly positive in RD. Therefore, DSP may be less crucial for RD formation than OPN.